Literature Review: Efektivitas Pemberian Madu pada Balita dengan Diare - Azzahra, Deah Nuraisyah; Nurhayati , Siti (Maternal & Neonatal Health Journal, 2026)
Diarrhea is one of the main causes of morbidity and mortality in toddlers, especially in developing countries. The use of honey as a complementary therapy has begun to be studied due to its antibacterial, anti-inflammatory, and nutritional content that supports the healing of digestive tract. To find out the effectiveness of honey administration on frequency reduction and improvement of diarrhea consistency in toddlers through review literature. The method used is literature review by searching articles through Google Scholar databases. There were 4 articles that met the inclusion criteria of analysis. The results show that the use of honey plays an important role in reducing the amount of diarrhea and improving the quality of feces in young children with diarrhea. Honey has the potential to be a safe and effective complementary therapy to support the treatment of toddler diarrhea.